The Emperor Jones - O'Neill, Eugene, 1888-1953 (B. I., 1979)
This 1933 adaptation of Eugene O'Neill's play features the great Paul Robeson in what many consider to be his finest performance on screen. Also starring Dudley Digges and Frank H. Wilson.